Adaptação marginal do agregado de trióxido mineral com e sem cloreto de cálcio em retrocavidades - Faria-Júnior, Norberto Batista [UNESP]; Bortoluzzi, Eduardo Antonio; Berbert, Fábio Luiz Camargo Villela [UNESP]; Tanomaru-Filho, Mario [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (My University, 2011)
Objective: To evaluate the marginal adaptation of the Mineral Trioxide Aggregate (MTA) with and without calcium chloride (CaCl2 ) in root-end cavities. Method: Twenty extracted single-rooted teeth were instrumented and obturated with gutta-percha and AH Plus. All roots were resected using a Zekrya bur and root-end cavities were prepared by using ultrasonic retrotips. Epoxy resin replicas of root-end surfaces after root-end cavity preparation were obtained, sputter coated with gold, and examined by using a scanning electron microscope (SEM). The samples were divided into two experimental groups (n = 10 teeth) according to the root-end filling material employed: G1 - MTA; and G2 - MTA + CaCl2 . After the root-end filling, the teeth were stored in moist gauze at 37 °C for 24 hours. New replicas of the root-end surfaces were obtained and examined under a SEM. Marginal adaptation of the filling materials were categorized as: 1) continuous margin; 2) non-continuous margin. Besides, percentages of continuous margin were calculated. The results were analyzed by the Mann-Whitney test. Results: Visible gaps were seen in 2 roots in G1 and in 3 roots in G2. A continuous margin was observed with 95,59% of MTA and 87,48% of MTA + CaCl2 root-end fillings. There was not statistical difference between the two groups (p > 0.05). Conclusion: The addition of CaCl2 to MTA did not alter its marginal adaptation capability to the dentin walls of root-end cavities.

Objetivo: Avaliar a adaptação marginal do Agregado de Trióxido Mineral (MTA) com e sem cloreto de cálcio (CaCl2 ) em retrocavidades. Método: Vinte dentes unirradiculados foram instrumentados e obturados com gutapercha e AH-Plus. Os ápices das raízes foram cortados com uma broca Zekrya e preparos retrógrados foram realizados com pontas ultrassônicas. Réplicas em resina dos ápices preparados foram obtidas, metalizadas com ouro e examinadas em microscopia eletrônica de varredura (MEV). Os espécimes foram divididos em dois grupos experimentais (n = 10 dentes), de acordo com o material retrobturador empregado: G1 – MTA e G2 – MTA + CaCl2 . Após as retrobturações, os dentes foram mantidos em ambiente úmido a 37 °C por 24 horas. Novas réplicas de resina foram obtidas e levadas ao MEV. A adaptação marginal dos cimentos foi classificada como: 1) margem contínua; 2) margem não contínua. Além disso, os percentuais de margem contínua foram calculados. Os resultados foram analisados pelo teste de Mann-Whitney. Resultados: Falhas de adaptação foram observadas em duas raízes no G1 e três raízes no G2. O percentual de margem contínua foi de 95,59% no grupo com MTA e 87,48% no grupo com MTA + CaCl2. Não houve diferença estatística significativa entre os dois grupos (p > 0,05). Conclusão: A adição do cloreto de cálcio ao MTA não alterou a sua capacidade de adaptação marginal às paredes dentinárias das retrocavidades
Marginal adaptation of the mineral trioxide aggregate with and without calcium chloride in root-end cavities
Keywords: Cirurgia bucal; Obturação retrógrada; Adaptação marginal dentária; Material retrobturador; Mineral trióxido agregado; Microscopia eletrônica de varredura